Meta‐Analysis of Time in Therapeutic Range in Continuous‐Flow Left Ventricular Assist Device Patients Receiving Warfarin. Issue 7 (6th March 2018) - Martinez, Brandon K.; Yik, Brenda; Tran, Raymond; Ilham, Sabrina; Coleman, Craig I.; Jennings, Douglas L.; Baker, William L.
Abstract: Continuous‐flow left ventricular assist devices (CF‐LVADs) prolong survival in advanced heart failure patients. Anticoagulation control is critical in CF‐LVAD patients due to increased thromboembolic and bleeding risk. We assessed the quality of INR control in CF‐LVAD patients measured by time in therapeutic range (TTR). We performed a systematic literature search of MEDLINE and SCOPUS through July 2017 to identify studies evaluating TTR in anticoagulated adult CF‐LVAD patients. Data on key characteristics and the TTR end point were then extracted from each study by two investigators using a standardized tool. Using a Hartung‐Knapp random effects model, a weighted mean TTR estimate with accompanying 95% confidence interval (CI) was calculated. Statistical heterogeneity was estimated using the I 2 statistic. Five published studies were included. All studies were single‐center, retrospective investigations that calculated TTR using the Rosendaal method. Sample sizes ranged from 11 to 115 patients (total of 270 patients) with durations of follow‐up ranging from 9 to 76 person‐years. On meta‐analysis, CF‐LVAD patients had a weighted mean TTR of 46.6% (95% CI: 36.0–57.3%, I 2  = 94%). This suggests that warfarin is difficult to manage in CF‐LVAD patients, which may contribute to high rates of bleeding and thromboembolic complications.